Development of a Fuzzy Logic Controller Algorithm for Air-conditioning System - Islam, Md. Shabiul; Sarker, Md. Shakowat Zaman; Rafi, Kazi Ashique Ahmed; Othman, Masuri (IEEE, 2006)
The goal of this paper is to develop an algorithm of fuzzy logic controller (FLC) for automatic air-condition controlling system. The Fuzzy logic system is used to design this algorithm. Two inputs and one output are designed with an industrial application in mind. This system consists of two sensors for feedback control: one to the monitor of temperature and another one to the monitor of humidity. There are three control elements: cooling valve, heating valve, and humidifying valve, to adjust the temperature and humidity of the air supply. Fuzzy rules are formulated by temperature and humidity. The model of this controller algorithm has been simulated using MATLAB simulation. Finally, the developed algorithm has been designed for implementing the hardware VLSI chip using VHDL language, from EDA tools.